(untitled) (Tempo e Argumento, 2011)
In the post WWI scenario, moral objectives were gradually joined to civic ones in the teaching of History. The 1920s were particularly marked by a comprehensive discussion about the role of education – mainly the teaching of History – in building world peace. School books were at the heart of this debate, where educators and opposite trends were able to voice their opinions. During these debates, the role of the Intellectual Cooperation International Commission (CICI) was outstanding in the League of Nations, the goal of which was to facilitate the collaboration of intellectuals working to foster world peace within the scope of the League’s objectives. This article addresses this context, emphasizing the role of Brazil in the adoption of a valid cultural diplomacy, both for European and Latin American countries, considering the change of focus from the interests of the League of Nations to the Pan-American Union. The participation of the Foreign Relations Ministry in this process is highlighted in this study, in that it undertook to endeavor a cultural diplomacy about the History to be taught, impervious to the political instability of that period and culminating with the publication of the “Bibliography of the History of Brazil”.